2011
DOI: 10.1128/aac.00466-11
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Study of the Epidemiology, Molecular Identification, and Antifungal Susceptibility of Candida parapsilosis, Candida orthopsilosis, and Candida metapsilosis Isolated from Patients with Candidemia

Abstract: A 13-month prospective multicenter study including 44 hospitals was carried out to evaluate the epidemiology of Candida parapsilosis complex candidemia in Spain. Susceptibility to amphotericin B, flucytosine, fluconazole, itraconazole, voriconazole, posaconazole, anidulafungin, caspofungin, and micafungin was tested by the microdilution colorimetric method. A total of 364 C. parapsilosis complex isolates were identified by molecular methods: C. parapsilosis (90.7%), Candida orthopsilosis (8.2%), and Candida me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
7
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 55 publications
11
111
7
14
Order By: Relevance
“…The majority of the patients analysed in this study were from the HSE and in this hospital the incidence was 28.6 % for C. orthopsilosis and 4.8 % for C. metapsilosis. These values are higher than those described in a multi-centre surveillance study conducted in Brazil between 2003 and 2004 (C. orthopsilosis was 9 % and C. metapsilosis was 3 %; Gonçalves et al, 2010), and those in a Spanish multi-centre study that reported 8.2 % of C. orthopsilosis and 1.1 % of C. metapsilosis (Cantó n et al, 2011). Our values are relatively similar to those recorded in a Spanish study in which 23.5 % of C. orthopsilosis and 2.1 % of C. metapsilosis were found (Garcia-Effron et al, 2012).…”
Section: Discussioncontrasting
confidence: 48%
“…The majority of the patients analysed in this study were from the HSE and in this hospital the incidence was 28.6 % for C. orthopsilosis and 4.8 % for C. metapsilosis. These values are higher than those described in a multi-centre surveillance study conducted in Brazil between 2003 and 2004 (C. orthopsilosis was 9 % and C. metapsilosis was 3 %; Gonçalves et al, 2010), and those in a Spanish multi-centre study that reported 8.2 % of C. orthopsilosis and 1.1 % of C. metapsilosis (Cantó n et al, 2011). Our values are relatively similar to those recorded in a Spanish study in which 23.5 % of C. orthopsilosis and 2.1 % of C. metapsilosis were found (Garcia-Effron et al, 2012).…”
Section: Discussioncontrasting
confidence: 48%
“…Among the azole derivatives analyzed in this study, FLC and VRC showed high levels of efficacy, as a single strain derived from the tongue showed SDD and SI to these drugs, respectively. And the MIC 50 and MIC 90 of both drugs was similar to that reported by other authors [2,17,18].…”
Section: Discussionsupporting
confidence: 77%
“…Caspofungin MICs were interpreted as follows: ≤2µg/mL, susceptible; 4µg/mL, intermediate; and ≥8µg/mL, resistant (11) (12) . Isolates with MICs of greater than 1µg/mL were considered resistant to AMB and POS, as suggested by Nguyen et al (13) and Cantón et al (3) .…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%
“…Amplifi cation of the SADH gene followed by BanI restriction enzyme digestion has been used as a rapid and reliable method with high discriminative power for C. parapsilosis complex species (6) (19) (20) (21) . Data have shown that these three species exhibit different prevalence rates, virulence, and in vitro antifungal susceptibility (3) (10) (19) (22) (23) (24) . In vitro studies have also shown that C. parapsilosis sensu stricto is more pathogenic than C. orthopsilosis, which is, in turn, is more pathogenic than C. metapsilosis (25) .…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%